2003
DOI: 10.1063/1.1589603
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic wave absorption property of carbon microcoils in 12–110 GHz region

Abstract: The electromagnetic (EM) wave absorption properties in the gigahertz region (12–110 GHz) of carbon microcoils (CMCs) with a three-dimensional-helical/spiral chiral structure (1–10 μm coil diameter and 0.1–10 mm coil length) were examined using the open space method. It was found that the target value of reflection loss, over −20 dB (above 99% absorptivity) necessitated for commercial applications, could be obtained for EM absorption composites of only 1–2 wt % addition of CMCs in a polyurethane matrix for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(71 citation statements)
references
References 19 publications
0
71
0
Order By: Relevance
“…These properties have led to the evaluation of helically shaped filaments with nano and micrometer coil diameters for use as tactile sensors, electromagnetic interference (EMI) shielding, and field emission devices [7,10,11]. In the early years, despite reports by several groups of successfully growing coiled carbon filaments, reproducing published results remained challenging.…”
Section: Open Accessmentioning
confidence: 93%
See 2 more Smart Citations
“…These properties have led to the evaluation of helically shaped filaments with nano and micrometer coil diameters for use as tactile sensors, electromagnetic interference (EMI) shielding, and field emission devices [7,10,11]. In the early years, despite reports by several groups of successfully growing coiled carbon filaments, reproducing published results remained challenging.…”
Section: Open Accessmentioning
confidence: 93%
“…Motojima et al [10] reported 12-110 GHz electromagnetic (EM) wave absorption of double helical CMC/polyurethane. As illustrated in Figure 19, the EM wave absorption property of this CMC composite was compared to other types of carbon composites.…”
Section: Electromagnetic Interference Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Electromagnetic properties: 23), 24) It is considered that the CMC is a promising candidate as a novel EM absorber, especially in the GHz range, because of its micro-coiling morphology. That is, the micro-coiling morphology is the most effective and ideal one for the generation of inductive current by Faraday's Law resulting in absorption of EM wave.…”
Section: Properties (A) Electric Propertiesmentioning
confidence: 99%
“…3.3.4 Electromagnetic Properties: [21][22][23][24] It is considered that the CMCs are promising candidates for use as EM absorbers, especially in the gigahertz (GHz) range, because of its micro-coiling morphology. In other word, the micro-coiling morphology is the most effective and ideal morphology for the generation of an inductive current by Faraday's Law resulting in absorption of EM wave.…”
Section: Electric Propertiesmentioning
confidence: 99%